2018
DOI: 10.1002/ijc.31271
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory potential of diet and risk of pancreatic cancer in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial

Abstract: Inflammation plays a central role in pancreatic cancer etiology and can be modulated by diet. We aimed to examine the association between the inflammatory potential of diet, assessed with the Dietary Inflammatory Index (DII®), and pancreatic cancer risk in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial prospective cohort. Our study included 101,449 participants aged 52-78 years at baseline who completed both baseline questionnaire and a diet history questionnaire. Energy-adjusted DII (E-DII)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
2
27
1
Order By: Relevance
“…6). Our findings agreed with previously conducted analyses using the prospective PLCO study, which reported an overall null association among 101,449 participants with baseline demographics similar to this study (7). Possible selection bias, frequent use of proxy responses, and other sources of information bias in pancreatic cancer case-control studies that may contribute to differential misclassification could help to explain differences in results from cohort studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6). Our findings agreed with previously conducted analyses using the prospective PLCO study, which reported an overall null association among 101,449 participants with baseline demographics similar to this study (7). Possible selection bias, frequent use of proxy responses, and other sources of information bias in pancreatic cancer case-control studies that may contribute to differential misclassification could help to explain differences in results from cohort studies.…”
Section: Discussionsupporting
confidence: 91%
“…The PLCO cohort suggested reverse causality for E-DII and pancreatic cancer association, where an inverse association between pro-inflammatory diets and pancreatic cancer risk was observed in follow up of <4 years (7). The current study did not support this phenomenon, even in the lag time analysis.…”
Section: Discussioncontrasting
confidence: 85%
“…Dietary assessment was similar to our previous study 48 . Diet was assessed by a self-reported food frequency questionnaire (FFQ), the DHQ version 1.0 (National Cancer Institute, 2007) introduced in 1998 to the control and intervention arms within a median of three years after randomization in this trial 49,50 .…”
Section: Dietary Assessmentsupporting
confidence: 64%
“…In a prospective cohort, in order to evaluate the E-DII and the risk for colorectal cancer in 190,963 individuals of both sexes and between 45 and 75 years old, Harmon et al [19] found an E-DII of -6.64 to 4.95. In another prospective cohort, Zheng et al [20] verified the survival rate of post-colorectal cancer women between 50 and 79 years old and the relationship with the E-DII. There was a variation of -6.8 to 3.25.…”
Section: Discussionmentioning
confidence: 94%